2012
DOI: 10.1111/are.12092
|View full text |Cite
|
Sign up to set email alerts
|

Partial to total replacement of fishmeal by poultry by-product meal in diets for juvenile rainbow trout (Oncorhynchus mykiss) and their effect on fatty acids from muscle tissue and the time required to retrieve the effect

Abstract: Triplicate groups of rainbow trout (Oncorhynchus mykiss) (1.4 ± 0.1 g) were fed experimental diets containing four levels of protein substitution to totally replace fishmeal with poultry by‐product meal (0, 33, 67 and 100%). Fishmeal (FM) from tuna fish by‐products and poultry by‐product meal ‘pet food grade' (PBM) were used. Diets were formulated to be isonitrogenous (43.5% crude protein) and isolipidic (12.5% crude fat). After 80 days of feeding, no significant differences were found in terms of thermal unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 29 publications
5
41
1
Order By: Relevance
“…Fatty acid analyses revealed that clear differences in fatty acids in muscle tissue from diet 100PBM, where levels of 16:0, 18:1n-9, and 18:3n-6 were signifi cantly higher, while 20:5n-3 and 22:6n-3 were lower. Similarly to these results, Parés-Sierra et al (2014) showed that rainbow trout feeding with PBM, resulted in lower 20:5n-3 and 22:6n-3 contents. The amount of Σ n-3 PUFA in the muscle of fi sh fed the 100PBM diet was 2.3%, while in control was 17.4%.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Fatty acid analyses revealed that clear differences in fatty acids in muscle tissue from diet 100PBM, where levels of 16:0, 18:1n-9, and 18:3n-6 were signifi cantly higher, while 20:5n-3 and 22:6n-3 were lower. Similarly to these results, Parés-Sierra et al (2014) showed that rainbow trout feeding with PBM, resulted in lower 20:5n-3 and 22:6n-3 contents. The amount of Σ n-3 PUFA in the muscle of fi sh fed the 100PBM diet was 2.3%, while in control was 17.4%.…”
Section: Discussionsupporting
confidence: 79%
“…It is well known that dietary fatty acid contents infl uences fatty acid composition in muscle of fi sh (Higgs et al 2006, Bahurmiz and Ng 2007, Borquez et al 2011. The results of the presently reported study, show that replacement of FM protein by PBM protein modifi ed the fatty acid composition of fi sh tissue (Table 3), as reported in previous studies (Gümüş and Erdogan 2010, Gümüş and Aydin 2013, Parés-Sierra et al 2014. Our fi ndings disagree with other studies which demonstrated that alternative protein sources did not infl uence fatty acid composition of fi sh (Gümüş 2011, Nogueira et al 2012).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Previous studies have considered that the PBM could not replace more than 50% of FM in diets for aquatic organisms (Gallagher & Degani, 1988;Fowler, 1991;Steffens, 1994). Nevertheless, results from recent studies have demonstrated that the replacement of FM by PBM has reached 100% in diets for several species of fish, without causing significant differences in performance parameters (Yang et al, 2006;Parés-Sierra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%